The impact of the Euro 2012 on popularity and market value of football players - Stephanie Kiefer (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2012)
High popularity and a high market value are important for a footballer's regular wage as well as advertising and sponsor contracts. Yet how can a football player improve his popularity and market value? The aim of this study is to examine whether a good performance during the 2012 European Football Championship has an impact on the increase of popularity in different online media and on market value and if so which specific performance variables are relevant for this. This study finds out that different Euro 2012 performance variables significantly influence the increase of popularity in selected online media and of market values. However, these performance variables mostly do not have the highest impact on the dependent variables. – – Eine hohe Popularität und ein hoher Markenwert sind wichtig für das reguläre Gehalt eines Fußballers sowie für seine Werbe- und Sponsorenverträge. Doch wie kann ein Fußballspieler seine Popularität und seinen Markenwert steigern? Das Ziel dieser Studie ist es zu untersuchen, ob gute Leistung während der Fußballeuropameisterschaft 2012 einen Einfluss auf die Popularität in verschiedenen Onlinemedien und den Markenwert hat und, falls ja, welche spezifischen Leistungsvariablen dafür relevant sind. Diese Studie kommt zu dem Ergebnis, dass verschiedene Leistungsvariablen einen signifikanten Einfluss auf den Anstieg an Popularität in den untersuchten Onlinemedien und Markenwert haben. Aber diese Leistungsvariablen haben meistens nicht den höchsten Einfluss auf die abhängigen Variablen.
Keywords: M30; J30; L82; L83; L86; 650